Anti-windup design of output tracking systems subject to actuator saturation and constant disturbances - Cao, Yong-Yan; Lin, Zongli; Ward, David G. (Automatica (Oxford), 2004)
This paper considers the design of output tracking systems subject to actuator saturation and integrator windup. An optimization-based approach is developed to design feedback and anti-windup gains of a controller structure involving intelligent integrators. The design goal is to increase stability region and output tracking and disturbance rejection ability of the closed-loop system.